Bibliometric analysis on current ergonomic trends in the international labor context - Jade Padrón-Sardiña; Isabela Pancorbo-Camacho; Juan Lázaro Acosta-Prieto; Yilena Cuello-Cuello (Dyna)
The objective of this research is to conduct a literature review on current ergonomic current ergonomic trends in the international labor context. The Prisma method was used and a total of 160 articles from 20 high impact journals selected from the Scimago Journal & Country Rank platform were examined from 20 high impact journals selected from the Scimago Journal & Country Rank platform were examined. The most relevant results were: there is a higher concentration of publications in the year 2023 (43.75%); the journals with the highest number of publications on Ergonomics are IEE Transaction on Human Machine systems (16.25%), in which Physical Ergonomics (53.67%) studied existing Ergonomics dimensions followed by Cognitive Ergonomics (36.03%). It is concluded that the emerging trends in Ergonomics reveal the current interest in bringing automation, artificial intelligence and new technologies to all areas of the human life.